2022
DOI: 10.1038/s41598-022-15406-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in TLR3, IL10 and CD209 influence the risk of BK polyomavirus infection after kidney transplantation

Abstract: Genetic determinants of BK polyomavirus infection after kidney transplantation remain poorly investigated. We assessed the potential impact of 13 different single nucleotide polymorphisms within genes mainly involved in innate immune responses on the risk of BKPyV viremia in 204 KT recipients. After a median follow-up of 1121.5 days, the cumulative incidence of any-level BKPyV viremia was 24.5% (50/204). There was a significant association between the minor T allele of TLR3 (rs3775291) SNP and the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…In contrast to the negative results observed for the post-transplant period, we found that the minor G allele of CD209 (rs4804803) in the homozygous state exerted a protective effect even after the Bonferroni correction, and that this association with undetectable TTV DNAemia at baseline remained significant after adjusting for clinical covariates. Although caution must be exercised due to the low number of patients with pre-transplant TTV DNA levels below the LLoD, this finding is in accordance with a recent study by our group showing a protective effect against BK polyomavirus viremia linked to the G allele of CD209 (rs4804803) after KT ( Redondo et al, 2022c ). In addition, the minor G allele has been also associated with a lower susceptibility to tuberculosis ( Vannberg et al, 2008 ) and severe dengue ( Sakuntabhai et al, 2005 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to the negative results observed for the post-transplant period, we found that the minor G allele of CD209 (rs4804803) in the homozygous state exerted a protective effect even after the Bonferroni correction, and that this association with undetectable TTV DNAemia at baseline remained significant after adjusting for clinical covariates. Although caution must be exercised due to the low number of patients with pre-transplant TTV DNA levels below the LLoD, this finding is in accordance with a recent study by our group showing a protective effect against BK polyomavirus viremia linked to the G allele of CD209 (rs4804803) after KT ( Redondo et al, 2022c ). In addition, the minor G allele has been also associated with a lower susceptibility to tuberculosis ( Vannberg et al, 2008 ) and severe dengue ( Sakuntabhai et al, 2005 ).…”
Section: Discussionsupporting
confidence: 91%
“…We have previously reported that certain SNPs in TLR9 (rs5743836, rs352139) modulate the risk of CMV infection in two independent cohorts of KT recipients ( Fernandez-Ruiz et al, 2015 ; Redondo et al, 2022b ). Regarding SNPs located in the CD209 gene, rs735240 appears to increase the incidence of CMV infection in seropositive KT recipients not receiving antiviral prophylaxis ( Fernandez-Ruiz et al, 2015 ), whereas rs4804803 has been correlated with an increased susceptibility to dengue virus ( Vargas-Castillo et al, 2018 ) and, more recently, BKPyV ( Redondo et al, 2022c ). We analyzed the SNPs located in IFNL4 (rs12979860, rs8099917) due to its well-established relevance in other viral infections, including CMV ( Fernandez-Ruiz et al, 2015 ) and hepatitis C virus (HCV) ( Ge et al, 2009 ; Thomas et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis carried out in this study explored the correlation between the rs3775291 polymorphism of the TLR3 gene and the risk of infection and disease development in different countries. Analyzing the six studies carried out on the European continent, most of them (83.33%) have shown an association between the presence of the ancestral allele (C) and the risk of infection, while one of them detected that the mutant allele (T) may be involved with the risk of developing a disease, as seen in BKPyV infection after kidney transplantation [30]. Regarding the analysis of data from three American [31][32][33] and nine Asian studies [13,24,[34][35][36][37][38][39][40], a significantly higher risk of infection with these diseases was found.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the literary scenario on associations between the investigated TLR3 SNPs and infections, several studies have already linked the rs3775291 SNP with infectious diseases ( Lee et al., 2013 ; Chen et al., 2017b ; Santos et al., 2019 ; Posadas-Mondragón et al., 2020 ; Redondo et al., 2022a ). A recent meta-analysis by ( Silva et al, 2023a ; Silva et al, 2023b ) summarized data found by primary research in several countries involving this SNP and infectious diseases.…”
Section: Discussionmentioning
confidence: 99%